Enhancing the prudential framework for securities firms - Jong Soo Hong (Korea Development Institute (KDI), 2025)
Despite increasing risk exposure from expanding assets and leverage among large securities firms, the current Net Capital Ratio (NCR) framework does not adequately capture these risks. To strengthen risk sensitivity while maintaining a balance between financial soundness and industry growth, the NCR formula for large securities firms should revert to its pre-2016 structure, and a differentiated regulatory approach tailored to business scope and risk characteristics should apply to small- and medium-sized firms.
Keywords: 330